Respon Pertumbuhan Tanaman Kailan (Brassica oleraceae L var alboglabra) Akibat Pemberian Kombinasi Pupuk NPK dan Pupuk Organik Cair Limbah Organik - Millah, Lilih Eka Ainul; Rahmi, Hayatul; Rianti, Winda (UNIVERSITAS LABUHANBATU, 2023)
Kailan (Brassica oleraceae L. var alboglabra) has great prospect for cultivation, however kailan’s low production needs improvement through proper and balanced fertilization. The study aimed to obtain a combination of NPK fertilizer and liquid organic fertilizer of organic waste that gived the best influence on th growth and yield of kailan. The research method used was an experimental method with a Single Factor Randomized Block Design (RBD) with 8 treatment combinations which is, A (300 kg/ha NPK Fertilizer and 0 ml/l Liquid Organic Fertilizer of Organic Waste), B (0 kg/ha NPK Fertilizer and 200 ml/l Liquid Organic Fertilizer of Organic Waste), C (200 kg/ha NPK Fertilizer and 100 ml/l Liquid Organic Fertilizer of Organic Waste), D (200 kg/ha NPK Fertilizer and 200 ml/l Liquid Organic Fertilizer of Organic Waste), E (200 kg/ha NPK Fertilizer and 300 ml/l Liquid Organic Fertilizer of Organic Waste), F (100 kg/ha NPK Fertilizer and 100 ml/l Liquid Organic Fertilizer of Organic Waste), G (100 kg/ha NPK Fertilizer and 200 ml/l Liquid Organic Fertilizer of Organic Waste), and H (100 kg/ha NPK Fertilizer and 300 ml/l Liquid Organic Fertilizer of Organic Waste). The results of this study showed that NPK fertilizer and liquid organic fertilizer of organic waste combination had significant effect on plant height aged aged 42. Treatment D gave the highest result on plant height aged 42 but treatment C is considered gave the best results in kailan’s growth and decreasing NPK fertilizer used. Keyword : Kailan, Liquid Organic Fertilizer of Organic Waste, NPK Fertilizer